Characterization of elastic properties of lacustrine shale reservoir using well logging and core analysis - Yu, H.; Wang, Z.; Rezaee, M. Reza; Arif, M.; Xiao, L. (2016)
© 2016 Society of Petroleum Engineers. All rights reserved. Understanding the elastic properties of rocks is very important for unconventional reservoirs exploration. Unlike marine shale, the lacustrine shale is more complicated with complex mineral composition and frequent sand and shale interbeds. Typical analysis for lacustrine shale gas reservoir rock include: triaxial test, X-ray diffraction (XRD), total organic carbon (TOC) measurements. The mineral composition is different for argillaceous shale and silty laminae shale. The static elastic properties are controlled by clay content, organic matter and porosity. In this work we evaluate elastic properties of above mentioned rocks using experimeal core analysis and well log data. Based on triaxial test, Young's modulus and Poisson's ratio of rocks are obtained by means of the relationship between strain and stress. Argillaceous shale is low to medium strength rock, and silty laminae shale belongs to medium to high strength rock. We find that Young's modulus and Poison's ratio has a negative relationship with clay content, organic matter and porosity which is present by bulk density and neutron porosity logs. The dynamic elastic properties are obtained from cross diploe acoustic well logging data. The dynamic elastic properties have the same controlling factors as static properties. Argillaceous shale and silty laminae shale have significantly different response characteristics in well logging. The porosity is the main factor which leads to the differences between dynamic and static elastic properties. Moreover, it is also found that the ratio of static and dynamic elastic properties is a function of porosity. Hence, density porosity and neutron porosity from the logs are chosen to establish dynamic elastic properties correction model. The correction model is effective in predicting static properties in lacustrine shale gas reservoirs. We conclude that the static properties obtained from the correction model match with core derived static properties.